Green polymer nanocomposites: bridging material innovation with sustainable industrial practices - Abu-Zurayk, Rund; Khalaf, Aya; Alnairat, Nour; Waleed, Haneen; Bozeya, Ayat; Abu-Dalo, Duaa; Rabba’a, Manar (Frontiers in Materials, 2025)
The global push for sustainability has sped up the shift from petroleum-based polymers to green polymer nanocomposites (GPNCs). These materials combine bio-based or biodegradable polymers with nanoscale reinforcements to boost performance and lessen environmental impact. This review discusses synthesis methods, structure–property relationships, and industrial uses of GPNCs. Natural polymers like starch, cellulose, chitosan, and alginate, along with bioplastics such as PLA, PHA, PBS, and PCL, offer biodegradability but have limited mechanical strength. This issue can be significantly addressed by adding nanofillers, like nanoclays, CNCs, nanofibers, biochar, and carbon materials. For example, the addition of nanofillers increased the modulus by (60-70)%, while surface-functionalized nanofillers enhanced interfacial bonding, and hybrid fillers blend stiffness with flexibility, resulting in a 200% increase in elongation at break. Some metal nanoparticles offer antimicrobial properties in which cell viability went down to less than 10% upon addition of nanofillers, or photocatalytic benefits, achieving 100% photocatalytic efficiency, with safety carefully evaluated. Advances in fabrication methods, including solution casting, melt compounding, in situ polymerization, electrospinning, and 3D printing, improve scalability and nanofiller distribution. Including nanofillers boosts mechanical and thermal properties for high-performance packaging. GPNCs are increasingly important in sectors: in packaging, for improved film strength; in automotive and aerospace, for lightweight designs; in construction, for coatings and structural parts; in water treatment, via enhanced membranes; and in biomedical devices, due to biocompatibility. GPNCs promote sustainability by utilizing waste, reducing energy use, and enabling recyclability or biodegradability, supporting circular economy goals. They meet regulatory defmands like the European Green Deal and EPR. Challenges include higher costs of bio-polymers and nanofillers, processing complexity, need for standardized testing, and toxicity concerns for certain nanomaterials. Despite these, green nanocomposites blend innovation and environmental responsibility, crucial for a sustainable future, with ongoing research promising broader industrial adoption.